2013
DOI: 10.1370/afm.1489
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Engaged Leadership Through a Learning Collaborative: Lessons From Primary Care Renewal in Oregon Safety Net Clinics

Abstract: PURPOSE The aim of this study was to explore how learning collaboratives cultivate leadership skills that are essential for implementing patient-centered medical homes (PCMHs). METHODSWe conducted an ethnographic evaluation of a payor-incentivized PCMH implementation in Oregon safety net clinics, known as Primary Care Renewal. Analyses primarily drew on in-depth interviews with organizational leaders who were involved in the initiative. We solicited perspectives on the history, barriers, facilitators, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…This unsustainable business model should be addressed by payment reform legislation or health system policies. 26,27 Similar to findings from other studies, 14,15,18 clinical and administrative leadership proved a crucial facilitator at the clinic level and higher. Our interviewees universally endorsed the need for leaders who were 1) inspiring and 2) able to effect fundamental operational changes.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This unsustainable business model should be addressed by payment reform legislation or health system policies. 26,27 Similar to findings from other studies, 14,15,18 clinical and administrative leadership proved a crucial facilitator at the clinic level and higher. Our interviewees universally endorsed the need for leaders who were 1) inspiring and 2) able to effect fundamental operational changes.…”
Section: Discussionsupporting
confidence: 77%
“…Our interviewees universally endorsed the need for leaders who were 1) inspiring and 2) able to effect fundamental operational changes. 14 The importance of facilitative leadership fits well with the concept of adaptive reserve (i.e., combination of healthy relationship infrastructure, alignment of management systems, and leadership), which Nutting et al observed as critical to managing practice change. 28 Minnesota has a high penetration of EMRs in primary care.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…LCs have most often been used to address challenges in ambulatory care settings or to address specific clinical topics, e.g. management of diabetes [1][2][3][4][5][6][7][8]. Antonini et al describes the use of a LC to address challenges faced in the integration of substance use diagnosis and treatment into primary health care and identify successful models and processes that minimize common barriers of documentation and privacy, financing and partnering with primary care providers [1].…”
Section: Introductionmentioning
confidence: 99%